Ispol'zovanie komp'juternych igr kak sredstva snjatija psichoemocional'nogo naprjaženija vysokokvalificirovannych sportsmenov-grebcov - Shubin, K. Yu.; Kosmina, E. A.; Makarov, A. A. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
The article considers the possibility of using computer games in the complex of rehabilitation measures in the training process of highly qualified athletes-rowers. The assessment of influence of computer games on a psychoemotional condition of athletes is made. The results of the study led to the conclusion that the use of computer games as a relieving means of emotional stress has a positive effect on the indicators of mood of the athletes. Computer games - as part of the complex of recovery measures allow us to increase the readiness of athletes to perform training tasks.